Studi Dampak Pendemi Covid-19 terhadap Proses Pembelajaran di Sekolah Dasar, Kecamatan Lubuk Raja, Kabupaten OKU, Sumatera Selatan - Jumali Jumali; Wahid Hasim; Reza Ariefka (Institute of Computer Science (IOCS), 2022)
This research aims to determine the impact of the Covid-19 epidemic on the learning process in elementary schools in Lubuk Raja District, OKU Regency, South Sumatra Province. This type of research is qualitative. In this study, the number of respondents was 10 teachers, 10 students, and 10 guardians. Respondents represent all schools in Lubuk Raja District. Primary data collection is done by giving questionnaires to respondents. The questions in the questionnaire were developed based on related literature. The results of this study are that there are several obstacles and expectations from teachers, guardians of students, and students regarding the learning process in elementary schools in Lubuk Raja District during the Covid-19 epidemic, there are still many who stutter with the on- line learning process,